2014
DOI: 10.1136/bmjopen-2014-005615
|View full text |Cite
|
Sign up to set email alerts
|

Potential risk of TNF inhibitors on the progression of interstitial lung disease in patients with rheumatoid arthritis

Abstract: ObjectivesBiological therapy represents important advances in alleviating rheumatoid arthritis (RA), but the effect on interstitial lung disease (ILD) has been controversial. The objective of this study was to assess the risk of such treatment for patients with ILD.DesignCase–control cohorts.SettingSingle centre in Japan.ParticipantsThis study included 163 patients with RA who underwent biological therapy.Outcome measuredWe assessed chest CT before initiation of biological therapy and grouped 163 patients acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 22 publications
1
51
0
Order By: Relevance
“…It is known that TNFα inhibitors promote subclinical interstitial lung disease. 12 In this study, the treatment in two patients using adalimumab and infliximab was terminated because of interstitial AC disease. Studies have shown that psoriasis is an independent risk factor in diseases such as diabetes, atherosclerosis, myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that TNFα inhibitors promote subclinical interstitial lung disease. 12 In this study, the treatment in two patients using adalimumab and infliximab was terminated because of interstitial AC disease. Studies have shown that psoriasis is an independent risk factor in diseases such as diabetes, atherosclerosis, myocardial infarction and stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Curtis et al [19] found that older patients, men, and patients with a history of other pulmonary disorders or recent exposure to glucocorticoids using tocolizumab, rituximab, abatacept, or anti-TNF-α agents were at increased risk for developing interstitial lung disease. The mechanisms of interstitial lung disease exacerbation after initiation of TNF-α-inhibitors are considered to be caused by the interaction of cytokine release upon these agents [20]. …”
Section: Discussionmentioning
confidence: 99%
“…4,5 There has been some evidence based on case reports, retrospective studies, and postmarketing surveillance that biologic DMARDs, particularly the anti-tumor necrosis factor (TNF) class, may be associated with an increased risk of pneumonitis. 1,[6][7][8] However, because no prospective controlled data exist and there is an appreciation that multiple variables, including the underlying CTD, are associated with ILD development, progression, or exacerbation, we suggest that these agents be used with caution in patients with CTD-ILD 1,[9][10][11] and other treatment options prioritized when possible. We frequently use the spectrum of biologic DMARDs in our patients with CTD-ILD to manage the extrathoracic manifestations and find that these agents often have minimal, if any, impact on the ILD.…”
Section: Management Of Extrathoracic Manifestationsmentioning
confidence: 95%